Implementasi Model Project Based Learning terhadap Hasil Belajar pada Mata Pelajaran Produk Kreatif dan Kewirausahaan (PKK) pada Kelas XI Jurusan Teknik Pemesinan di SMK Dhuafa Padang - Putrarianda, Mexi; Jasman, Jasman; Primandari, Sri Rizki Putri; Primawati, Primawati (Al-DYAS, 2025)
This research is motivated by the low learning outcomes of students in the subject of Entrepreneurship Creative Products. Teachers still cannot carry out the learning process properly and optimally. This results in student learning outcomes. This study aims to describe the making of door trellis with the Project Based Learning model in the learning process to improve the learning outcomes of Entrepreneurship Creative Products at SMK. This type of research is classroom action research (PTK) using qualitative and quantitative approaches. The subjects of this research were students of class XI SMK Dhuafa Padang with 25 students, researchers as practitioners and class teachers as observers. This research was conducted in two cycles, which consisted of planning, implementation, observation and reflection. Research data obtained from observations of the learning process, tests in the form of evaluation sheets done by students, and non-tests taken from observations of students' skills. In cycle I learning outcomes obtained a percentage of 52% and cycle II obtained a percentage of 96% completeness with very good qualifications. Thus it can be concluded that learning Entrepreneurial Creative Products making door trellis with Project Based Learning model can improve learning outcomes.